Evaluation of improved CT‐based hardware attenuation correction in PET/MRI: Application to a 16‐channel RF breast coil. Issue 4 (21st February 2022) - Lindemann, Maike E.; Oehmigen, Mark; Lanz, Titus; Grafe, Hong; Bruckmann, Nils Martin; Umutlu, Lale; Quick, Harald H.
Abstract: Purpose: The aim of this study was to compare and evaluate three different bilinear conversion curves for attenuation correction (AC) of a 16‐channel radiofrequency (RF) coil in positron emission tomography/magnetic resonance (PET/MR) breast cancer imaging. Methods: The quantitative impact of three different bilinear conversions of computed tomography (CT) data for the AC of a 16‐channel RF breast coil was systematically evaluated in phantom measurements and on n = 20 PET/MR patients with breast cancer. PET data were reconstructed four times: (1) no coil AC (C‐NAC) serving as a reference, (2) established bilinear conversion by Carney et al., (3) bilinear conversion by Paulus et al., and (4) bilinear conversion by Oehmigen et al. Relative differences in PET data were calculated. Results: Independent of the choice of bilinear conversion, significant gains in PET signal, compared to C‐NAC, were measurable in all phantom and patient measurements. Mean relative differences of ca. 10% in SUVmean (i.e., standardized uptake value; maximal relative differences up to 30%) due to the integration of the coil AC were calculated, compared to C‐NAC in phantom and patient measurements. Relative difference images depict that the quantitative impact of coil AC is highest in regions close to the RF coil when compared to no AC data. Bilinear conversion by Carney et al. shows a slightly overcorrection (2.9%), whereas the conversion by Paulus et al. provides a slight undercorrection of the PET images (−1.6%) in comparison to the no‐coil measurement. The bilinear conversion proposed by Oehmigen et al. provides the most appropriate AC for the breast coil in this phantom experiment (−0.2%). A total of 23 congruent lesions could be detected in all patients. All lesions could be detected in all reconstructions. Conclusions: For the best possible PET image quality and accurate PET quantification in breast PET/MRI, the AC of MR hardware components is important. The bilinear conversion proposed by Oehmigen et al. provides the most appropriate AC for the breast coil in this study.